A New Optimization Model for Rotary-Wing Air Vehicle Propeller Design - Ucar, Ukbe; Tanyerı, Burak; Bayrak, Zehra Ural (My University, 2025)
IIn this study, the propeller characteristics of the aircraft have been optimized in terms of stabilization and manoeuvrability and it has been aimed to find the ideal propeller dimensions for the aircraft. A mathematical modelling has been developed for optimization and four different objectives are simultaneously optimized in the model. The results have been compared with simulation, analysis and real results. Gams and MATLAB programs have been used for developed mathematical model and simulation algorithm, respectively, and ANSYS program has been also used for CFD analysis. It has been observed that CFD analysis and mathematical model results are parallel to each other. As a result of the analysis, thanks to the developed model, a 6.47% improvement has been achieved in efficiency compared to the existing propeller system. In addition, an improvement of 3.93 times in “thrust” and 3.86 times in “total lift force” has been provided. Finally, it has been reported that the total drag force has been successfully minimized.
Keywords: Optimization; Simulation; CFD Analysis; Aviation; Aircrafts; Propeller design